AN INNOVATIVE APPROACH TO THE MANAGEMENT STRATEGY OF CHRONIC ENDOMETRIOSIS IN WOMEN OF REPRODUCTIVE AGE - Umida J. Hamroyeva (Central Asian Journal of Medicine, 2024)
Chronic endometriosis poses significant challenges in the management of women's reproductive health. This study introduces an innovative approach to the management strategy of chronic endometriosis in women of reproductive age. The research aims to address the limitations of conventional treatment methods and improve outcomes for patients with this debilitating condition. Materials and methods involved the implementation of a multidisciplinary approach, incorporating medical, surgical, and complementary interventions. Results indicate promising outcomes in symptom management, fertility preservation, and quality of life enhancement. This study underscores the importance of a comprehensive and personalized approach to the management of chronic endometriosis.